Anthropometric study on inner canthal distance and outer canthal distance in adult Bangladeshi people - Kawser, Tunajjina; Alam, Md Rafiqul; Tripti, Durratul Jannat; Chowdhury, Mahfuza; Singha, Partha Sarathi (Bangladesh Journal of Anatomy, 2020)
Context: Inner canthal distance and outer canthal distance are important parameters in craniofacial anthropometry. Various studies have been conducted on anthropometric measurement of the canthal distance from different parts of the world. These studies prove that much variability exist depending on age, sex, race and genetic background. Knowledge of normal canthal distance is necessary for plastic and reconstructive craniofacial surgeons and ophthalmologists for correction of craniofacial and ocular defect, implanting prosthesis and cosmetic purpose. Materials and Methods: A cross sectional and analytical study was conducted on 55 adult male and 55 adult female Bangladeshi people age ranging from 18-35 years in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2017 to June 2018. Inner and outer canthal distance is measured by round end spreading caliper. Comparison of measurement was done by unpaired Student’s‘t’ test. Results: The result revealed that the mean inner and outer canthal distance were significantly (p<0.001) higher in male than female. Conclusion: The study showed there is sexual dimorphism in inner and outer canthal distance among adult Bangladeshi people. Bangladesh Journal of Anatomy January 2020, Vol. 18, No. 1, pp. 3-6